The Constructed Body in a Disembodied Platform: Interdisciplinarity and Team Teaching in the Age of Covid-19 - Wu, Jennifer (The sixteenth century journal, 2020)
In this article the authors offer a personal narrative of their experiences teaching a remote college-level course during the COVID-19 pandemic, noting their experiences transitioning to remote learning and details relating to their course, titled "In the Flesh: The Constructed Body in Medieval and Renaissance Europe."